Effectiveness of Teachers’ Creative Skills Using Analogy in Learning of the Concept of Basic Electric Circuits - Ponto, Hantje (International Journal of Psychosocial Rehabilitation, 2020)
Basic electric circuits (BEC) are major subject matter in the Electricity Skills Engineering competency study program at the Vocational Technical School (VTS) in Indonesia. Because electricity is an abstract phenomenon, resulting in students often have difficulty learning BEC which results in a misunderstanding of concepts or known as misconceptions. One factor occurs misconceptions because teachers use conventional teaching. Creative teaching skills using analogy are methods of teaching to change students' misconceptions on BEC subject matter. The research objective is to compare the creative skills of teaching using analogies with conventional teaching. This study uses a quasi-experimental method. The research subjects were 67 students who attended the VTS Electricity Engineering competence consisting of 34 students as an experimental group, and 33 students as a control group. Research findings indicate the experimental group is more effective than the conventional group.